2014
DOI: 10.1002/bmc.3189
|View full text |Cite
|
Sign up to set email alerts
|

Development and thermodynamic evaluation of novel lipid raft stationary phase chromatography for screening potential antitumor agents

Abstract: Novel lipid raft stationary phase chromatography (LRSC), with lipid rafts that contain abundant tropomyosin-related tyrosine kinase A receptors immobilized on the stationary phase, was developed for a high-throughput screening of potentially active antitumor agents. Lestaurtinib was used as a model compound to determine the operational parameters of the LRSC. Of all the factors considered, the particle size of column packing, the column temperature and the flow rate were of immense importance in determining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This also confirms a different molecular target for Gemcitabine and further strengthened the high selectivity of the affinity system. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 11 bioactive isolates via LRSC analysis, it can be said that the two Chinese herbs had some form of interactions with TrkA receptor as reported in similar studies [18,19].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This also confirms a different molecular target for Gemcitabine and further strengthened the high selectivity of the affinity system. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 11 bioactive isolates via LRSC analysis, it can be said that the two Chinese herbs had some form of interactions with TrkA receptor as reported in similar studies [18,19].…”
Section: Discussionsupporting
confidence: 52%
“…For instance, cytotoxic bisdesmosides (Segetoside H and I) from the seeds of Vaccaria segetalis exhibited IC 50 at lower micro-molar level similar to the clinically utilized drug cisplatin against MDA-MB-261 breast cancer cells [23]. It is also likely that the effect could be enhanced on other cancer cells, particularly U251 gliocoma cells from which the LRSC was developed as witness in previous studies [18,19]. Notwithstanding these findings, the results still support the fact that in the absence of commonly employed conventional assays for assessing the viability of cancers.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our laboratory has been able to screen periplocymarin with antitumor effect from Cortex periplocae by lipid-raft chromatography, which was found to be linked to the tyrosine kinase receptor [6]. It has been reported that periplocymarin strongly inhibited proliferation of PC3, U937, HCT-8, Bel-7402, BGC823, A549 and A2780 cell lines in vitro with IC 50 values of 0.02–0.29 μM [7].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2000) utilized immobilized human serum albumin to screen the bioactive compounds from Artemisia capillaris and confirmed two strong retention peaks of scoparone and capillarisin. Tong et al (2014) extracted lipid rafts from brain glioma U251 cells by synthesizing immobilized lipid to screen for anti-tumor bioactive compounds from Galla chinensis . Despite their great contribution to promote the development of TCM-guided drugs, the aforementioned reports appear to have certain limitations, like lower separating capacity and specificity.…”
Section: Resultsmentioning
confidence: 99%